Climate change and conservation of threatened tree species in the Doce River Basin: an ecological niche modeling approach - Cecília Loren-Silva; Rodrigo Gomes Gorsani; Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Rafaela Brandão-Gomes; Renato Augusto Ferreira de Lima; Carlos Moreira Miquelino Eleto Torres; Nathália Silva; Marcelo Simonelli; Markus Gastauer; Fabiana Bonani; João Augusto Alves Meira-Neto (Biodiversity and Conservation, 2026)
Tropical forests, particularly the Atlantic Forest, are among the most biodiverse and threatened ecosystems on Earth. Intense fragmentation, historical deforestation, and climate change have compromised their integrity and endangered endemic and rare species. The situation is even more critical in the Doce River Basin (DRB), a biodiversity hotspot in southeastern Brazil, due to the expansion of pastureland and mining, as well as the 2015 Mariana disaster. Understanding how future climate may affect the persistence of threatened tree species in the region is essential. This study evaluated the effects of climate scenarios on the distribution of 26 rare and/or threatened tree species in the DRB. We used Species Distribution Models (SDMs), combining algorithms (GLM, RDF, SVM, MaxEnt) into a consensus ensemble model under SSP3-7.0 and SSP5-8.5 scenarios for 2050 and 2090. Climatic, topographic, and edaphic variables were predictors, with climate explaining most environmental variation. Among the 26 species, 19 are projected to lose over 75% of their suitable area, with local extinction likely for range-restricted and specialized species such as Handroanthus arianeae and Grazielodendron rio-docensis . Species associated with mature forests and humid microclimates were most severely affected, while some generalists showed resilience, maintaining or expanding suitable areas. Although all species retain some suitable habitats within Protected Areas (PAs), results indicate the current PA network will be insufficient for long-term conservation. Complementary strategies such as assisted translocation, habitat connectivity, and priority-area identification based on climate projections are needed. This study provides critical insights for policies and land-use planning aimed at conserving the DRB’s threatened flora.

Urban flood exposure assessment through citizen science, 2D hydraulic modeling, and artificial intelligence - Rodrigo Rodríguez; Agustin Robles-Morua; Diana Meza-Figueroa; José Tuxpan-Vargas; Rodolfo Cisneros Almazán; Nancy Perez Ramos; Bhaskar Sen-Gupta; Nadia Martínez-Villegas (Journal of Environmental Management, 2025)

An assessment of potential interventions to reduce the totoaba illegal trade market - Rodrigo Oyanedel; Erendira Aceves‐Bueno; Lucia Davids; Miguel Ángel Cisneros‐Mata (Conservation Biology, 2024)
The illegal trade in totoaba ( Totoaba macdonaldi ) is causing adverse social, ecological, and economic impacts. This illegal activity is accelerating the overexploitation of totoaba and pushing the critically endangered vaquita ( Phocoena sinus ) closer to extinction. Despite extensive efforts to recover vaquita populations, scant attention has been given to the totoaba trade as an independent issue. As a result, data on the totoaba trade are limited, which hampers robust analyses and development of effective interventions to reduce illegal harvesting. We used a previously developed framework specifically designed to examine dynamics of illegal markets and guide measures to mitigate illegal use of totoaba. This framework separates markets into 3 analytical levels: characterization of participating actors (e.g., fishers, intermediaries); examination of how actors interact within the market (e.g., organization of supply chains); and assessment of the overall market dynamics that result from these interactions (e.g., factors determining price and quantity). We reviewed existing literature (108 initial articles) and interviewed key market actors, academics, and nongovernmental organization experts (14) to obtain data for this framework. Our findings offer an overview of the totoaba illegal market operation, highlighting intervention points (e.g., customs agents) and areas where additional information is required to decrease information gaps (e.g., US local market). We describe the structure and complexity of this market, emphasizing the influential role of organized crime in shaping its dynamics (e.g., controlling prices paid to fishers and stockpiling). By providing a systematic and in‐depth understanding of the market operation, we aimed to establish a benchmark for effective interventions and future research aimed at reducing uncertainties. Our results provide a crucial step toward addressing this critical issue and can help facilitate development of effective strategies to combat the illegal totoaba trade and promote biodiversity conservation more broadly.

Influence of human emotions on conservation attitudes toward relevant wildlife species in El Triunfo Biosphere Reserve, Mexico - Nathalia M. Castillo-Huitrón; Eduardo J. Naranjo; Dídac Santos-Fita; Mateo Peñaherrera-Aguirre; Pavol Prokop; Rodrigo Cisneros; Silvia Vaca Gallegos; Zuzana Ježová (Biodiversity and Conservation, 2024)

Study of a light hydrocarbon fraction spill migration that occurred in an area of the Mexican southeast using computational fluid dynamics - Miguel Ángel Arellano-González; Pedro López-Ordaz; Dulce María Palmerín-Carreño; Jorge Gracida-Rodríguez; María Belem Arce-Vázquez; Analiz Mondragón-Cisneros; Rodrigo Melgarejo-Torres (Environmental Science and Pollution Research, 2023)

Habitat requirements and differential abundance of the culpeo (Lycalopex culpaeus) in the high Andes of southern Ecuador - Marta Guntiñas; Jorge Lozano; Rodrigo Cisneros; Carlos Narváez; Daniela Arias (European Journal of Wildlife Research, 2019)

Molecular species identification for multiple carnivores - Marta De Barba; Jennifer R. Adams; Caren S. Goldberg; Carisa R. Stansbury; Daniela Arias; Rodrigo Cisneros; Lisette P. Waits (Conservation Genetics Resources, 2014)